Metarhizium-Inoculated Coffee Seeds Promote Plant Growth and Biocontrol of Coffee Leaf Miner - Jéssica Letícia Abreu Martins; Mayara Loss Franzin; Douglas da Silva Ferreira; Larissa Cristina Rocha Magina; Elem Fialho Martins; Laís Viana Paes Mendonça; Wânia dos Santos Neves; Angelo Pallini; Fernando Hercos Valicente; Jason M. Schmidt; Simon Luke Elliot; Madelaine Venzon (Microorganisms)
Metarhizium (Hypocreales: Clavicipitaceae) has a multifunctional life cycle, establishing as a plant endophyte and acting as entomopathogenic fungi. Metarhizium robertsii and Metarhizium brunneum can be associated with coffee plants and provide enhanced protection against a major pest of coffee, the coffee leaf miner (CLM) (Leucoptera coffeella). This association would be an easily deployable biological control option. Here we tested the potential of inoculating coffee seeds with M. robertsii and M. brunneum collected from the soil of coffee crops in the Cerrado (Brazil) for control of the CLM and the enhancement of plant growth with a commonly used fungicide. We conducted the experiment in a greenhouse and after the seedlings grew, we placed them in a cage with two couples of CLMs. We evaluated the CLM development time, reproduction, and plant growth traits. We observed a longer development time of CLMs when fed on plants inoculated with both isolates. In addition, the CLMs laid fewer eggs compared to those fed on plants without fungal inoculation. Plant growth was promoted when seeds were inoculated with fungi, and the fungicide did not affect any evaluated parameter. Coffee seed inoculation with M. robertsii and M. brunneum appears to provide protection against CLMs and promote growth improvement.